2022
DOI: 10.1021/acscatal.1c04959
|View full text |Cite
|
Sign up to set email alerts
|

Photo–Thermo-Dual Catalysis of Levulinic Acid and Levulinate Ester to γ-Valerolactone

Abstract: Herein, we developed photo–thermo-dual catalytic strategies for the production of γ-valerolactone (GVL) from levulinic acid (LA) and its ester using platinum-loaded TiO2 as a dual-functional catalyst. Both catalytic systems were evaluated under mild reaction conditions. In the photocatalysis system, a base plays crucial roles in the conversion of LA and EL to GVL. The control experiments reveal that plausible mechanistic pathways of both systems proceed via the hydrogenation of the ketone group of LA to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…164 Photo catalysts reported in literature were evaluated using isopropanol, ethanol, and 2-propanol as H 2 donor. [155][156][157]165 These studies should direct toward testing FA decomposition for in situ H 2 production in the presence of photo catalyst.…”
Section: Discussion and Further Research Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…164 Photo catalysts reported in literature were evaluated using isopropanol, ethanol, and 2-propanol as H 2 donor. [155][156][157]165 These studies should direct toward testing FA decomposition for in situ H 2 production in the presence of photo catalyst.…”
Section: Discussion and Further Research Recommendationsmentioning
confidence: 99%
“…Nevertheless, the addition of NaOH base promoted GVL yield up to 95% using ethanol as a green solvent. 155 Noble metals Pt, Pd, & Au-loaded TiO 2 photo catalyst were screened by Zhang H. et al for hydrogenation of LA into GVL in presence of isopropanol. The corresponding order of LA conversion was Pt/TiO 2 < Pd/TiO 2 < Au/TiO 2 of 69% (69.5% GVL yield), 71% (76.4% GVL yield), and 79% (85.3% GVL yield), respectively.…”
Section: Catalytic Hydrogenation Of La Using Different H2 Sourcesmentioning
confidence: 99%
“…Bunrit et al showed that Pt/TiO2 acts as thermo-and photo-catalyst for converting levulinic acid and its ester into g-valerolactone in mild conditions using 2-propanol as hydrogen donor [22]. However, they did not exploit this dual-functional character to explore the reaction under a dual-mode excitation.…”
Section: Valorization Of Bio-resourcesmentioning
confidence: 99%
“…[1][2][3] It can be harvested using a range of ever-evolving technologies, such as photovoltaics, [4][5][6][7] water distillation, [8][9][10][11][12][13][14] molten salt technology, 15 and artificial photosynthesis. 16,17 Of the several solar energy converting methods, solar chemical conversion, including photocatalysis [18][19][20][21][22][23][24] and photothermal catalysis, are regarded as very promising technologies to produce chemical products. 25 Photothermal catalysis, where solar energy is converted into heat to maintain a needed temperature and a thermal catalyst is used to drive the reaction, has attracted great attention owing to its high solar utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The direct utilization of solar energy as an alternative to fossil fuels is propitious to carbon‐neutral target realization 1–3 . It can be harvested using a range of ever‐evolving technologies, such as photovoltaics, 4–7 water distillation, 8–14 molten salt technology, 15 and artificial photosynthesis 16,17 . Of the several solar energy converting methods, solar chemical conversion, including photocatalysis 18–24 and photothermal catalysis, are regarded as very promising technologies to produce chemical products 25 …”
Section: Introductionmentioning
confidence: 99%